Idiosyncratic chloroquine retinopathy â a case report (Faculty of Medicine Universitas Indonesia, 2002)
Chloroquine still remains the most widely used antimalarial of present time. Cumulative dose retinopathy has been reported with the use of chloroquine therapy, especially seen in patients on its chronic therapy in rheumatological disorders. A rare case report on chloroquine induced idiosyncratic retinopathy while being used in treatment of Falciparum malaria is being presented.Â (Med J Indones 2002; 11: 176-8)Keywords: cloroquine, adverse effects, idiosyncratic, malaria, retinopathy